القبض الحكمي في النقود الإلكترونية في القانون الإندونيسي والآثار المترتبة عليه : دراسة فقهية تقويمية - Raushan Fikry Adam (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This research aims to show the extent to which the constructive possession has been achieved in electronic money, based on the regulations issued by the Central Bank of Indonesia related to it. It aims to highlight the extent to which Indonesian law in electronic money is consistent with the concept of possession in Islamic Jurisprudence. By evaluating the Indonesian Law on electronic money with the concept of possession among Fiqh Scholars, we can reveal the legality of using electronic money in Islamic Law. Because electronic money, with its large number of users, has left some controversial decisions in society. Among the controversial decisions issued by the Central Bank of Indonesia was bank regulation no. 20/6 / PBI / 2018; That the electronic money card issuer does not guarantee the cash value contained on the card when the card is lost from the holder. As well as a central bank decision that allows electronic money issuers to collect fees from users when topping up the balance. This research relied on the inductive approach in collecting data from the existing and available sources, and an analytical method in studying the data represented and the elements related to the topic. This research achieved several results, the most prominent of which are: The character of electronic money in Indonesia is related to the legal character that arises from the relationship between parties in electronic money. And the Central Bank of Indonesia regulation that allows issuers not to guarantee the value of unregistered electronic money when it is lost does not affect the legality of using electronic money under Islamic law. Because it does not contradict the possession theory in Islamic jurisprudence. Likewise, the central bank's decision to charge customers when topping up electronic money does not affect the legality of using electronic money. Because this fee is for services provided by the issuer to customers and is included in the lease agreement. And in the end, the researcher recommends the following: inviting Muslim researchers to thoroughly research the achievement of constructive possession in contemporary banking problems. Because possession has a close relationship with the contract, and knowing about the possession theory is important because we can know the obligations of all parties that arise after the contract through knowledge of the theory of possession.